Familial chromosomal translocation X; 22 associated with infertility and recurrent X mosaicism. Issue 1 (December 2016) - Grzesiuk, Juliana; Pereira, Ciro; Grangeiro, Carlos; Picanço-Albuquerque, Clarissa; Oliveira-Gennaro, Flávia; Machado, Filipe; Medina-Acosta, Enrique; Ramos, Ester; Yoshimoto, Maisa; Martelli, Lucia
Abstract Background Individuals with apparently balanced translocations, often, show no clinical findings. However, in meiosis, translocations tend to cause errors on chromosome disjunction and the ones involving sex chromosomes have particular implications for the phenotype. Male carriers of balanced X-autosome translocations are almost invariably infertile due to interruption of the spermatogenesis, but the mechanism is not fully understood. Case presentation In this case report, we performed a combination of classical cytogenetics (G-banding), molecular cytogenetics (fluorescence in situ hybridization and X-chromosome inactivation study), and cytogenomics (microarray-based comparative genomic hybridization) techniques for characterization of an inherited (X;22) translocation in a family originally referred for infertility investigation. Both proband and his sister are infertile and present the maternally inherited translocation. Interestingly, the maternal grandmother was mosaic for X chromosome monosomy suggesting that the t(X;22) in the proband's mother arose by errors at oogenesis. The presence of the same mosaicism of the X chromosome in the proband's aunt is consistent with this consideration. Array- CGH analysis showed no constitutional pathogenic gains or losses in the translocation carriers. The X-chromosome inactivation studies revealed that the translocated X;22 was active in 99.3% of cells in the mother and in 88% of cells in the daughter. We suggest that incomplete skewing of X inactivation (>97 %) of the daughter could justify the infertility. This study is the first description of recurrent mosaicism of the X chromosome associated with a familial X-autosome translocation. Conclusions The phenotype of infertility was probably caused by disruption of spermatogenesis due to gametogenesis specific errors resulted from meiotic pairing and segregation anomalies on the translocated chromosomes.